Literacy Practices of Tamil Youth in Singapore (International Journal of Language, Literacy and Translation, 2025)
This study analyses the literacy skills of Singapore youth in Tamil and their experiences with literacy. Despite Tamilbeing one of the four official languages in Singapore, the community is documented to be experiencing language shift(Gopinathan, Lakshmi, & Saravanan, 2019). It is therefore important to understand the factors that influence theacquisition of literacy practices at various stages of one’s life. To do so the study adopts Barton’s (2007) ecologicalframework of analysing reading and writing skills through three stages: home (emergent), school and youth and ifyouth literacy practices were influenced by emergent and school literacy practices. Interviews were conducted withten Tamil youth between 21-30 years of age from varied backgrounds to understand their language learningexperiences at the three different stages. This study reveals that the literacy practices of youth are influenced by homesupport, religious practices and parents’ attitude towards the language more than school practices. The finding ofthis study can inform researchers in the field of language maintenance and shift studies to use Barton’s framework ofliteracies as an additional methodology.